Optimasi Formula SNEDDS (Self Nanoemulsifying Drug Delivery System) Minyak Atsiri Bawang Putih - Linda Nur'Aini; Sani Ega Priani; Ratih Aryani (Bandung Conference Series: Pharmacy, 2024)
Abstract. Garlic essential oil is known to contain compounds that can play a role in reducing cholesterol in the body. SNEDDS (Self Nanoemulsifying Drug Delivery System) is a delivery system development for drugs with poor solubility. The SNEDDS component consists of a mixture of oil, surfactant and co-surfactant which will form an O/W nanoemulsion (oil in water) spontaneously when mixed with water accompanied by light stirring. The aim of this research is to obtain a formulation for SNEDDS for garlic essential oil. SNEDDS is formulated using garlic essential oil as the oil phase, tween 20 as the surfactant, and propylene glycol as the co-surfactant. Abstrak. Minyak atsiri bawang putih diketahui mengandung senyawa yang dapat berperan dalam penurunan kolesterol pada tubuh. SNEDDS (Self Nanoemulsifying Drug Delivery System) adalah salah satu pengembangan sistem penghantaran untuk obat dengan kelarutan yang kurang baik. Komponen SNEDDS terdiri dari campuran minyak, surfaktan, dan ko-surfaktan yang akan membentuk nanoemulsi M/A (minyak dalam air) secara spontan ketika bercampur dengan air disertai dengan pengadukan yang ringan. Tujuan dari penelitian ini yaitu untuk untuk memperoleh formulasi SNEDDS minyak atsiri bawang putih. SNEDDS diformulasikan menggunakan minyak atsiri bawang putih sebagai fase minyak, tween 20 sebagai surfaktan, dan propilenglikol sebagai ko-surfaktan.